Global, regional, and national burden of early-onset colorectal cancer attributable to high BMI (1990–2021) - Zhang, Yin; Han, Fuzhou; Qu, Jun (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to assess the global, regional, and national burden of early-onset colorectal cancer (EO-CRC) attributable to high body mass index (BMI) from 1990 to 2021. By examining demographic, geographic, and sex-specific disparities, the goal was to elucidate trends and inform targeted prevention strategies.MethodsWe utilized data from the Global Burden of Disease (GBD) 2021 study, applying population-attributable fraction modeling to estimate disability-adjusted life years (DALYs) linked to high BMI (≥25 kg/m2). Analyses were stratified by sex, age, socio-demographic index (SDI), and geography. Temporal trends were assessed using Joinpoint regression, and future projections were estimated via Bayesian Age-Period-Cohort (BAPC) modeling. Decomposition and frontier analyses were conducted to identify key drivers of change and benchmark national performance.ResultsGlobally, age-standardized DALY rates (ASDRs) for EO-CRC attributable to high BMI increased from 8.07 per 100,000 in 1990 to 10.49 in 2021. The burden was consistently higher and increased more rapidly among males. While high SDI countries experienced stabilization or even decline in rates after 2017, sharp increases were observed in low-middle and low SDI countries. Population growth and epidemiological transitions were the primary contributors to DALY increases. Projections suggest further growth in burden, especially among males and in lower SDI regions.ConclusionHigh BMI plays a substantial role in the rising global burden of EO-CRC, with pronounced disparities across regions and sexes. The shifting burden toward low and middle SDI countries, along with accelerating trends among men, highlights the urgent need for sex- and region-specific obesity prevention and early screening strategies to mitigate the growing public health impact of EO-CRC.